Optimization and Control of Economic Dispatch for Power Systems - Ab Ghani, Mohd Ruddin (1993)
This paper presents a model and a solution scheme for optimizing and control of an economic and secure dispatch system for power systems. The formulation caters for loading and deloading rates, limits on generators outputs, spinning reserve requirements and group power import-export limits. The modelling strategy and solution techniques employed are based on Dantzig-Wolfe Decomposition principle, which produces a master problem solved by revised simplex method and a capacitated transshipment subproblem solved by network flow algorithm. The computational efficiency of the algorithm was achieved and this makes it suitable for an on-line dispatch.